ADHD: prevalence and effect on opioid use disorder treatment outcome in a French sample of patients receiving medication for opioid use disorder-the influence of impulsivity as a mediating factor - Auxane Beslot; Marie Grall-Bronnec; Marianne Balem; Benoit Schreck; Edouard-Jules Laforgue; Caroline Victorri-Vigneau; Morgane Guillou-Landreat; Juliette Leboucher; OPAL-Group; Gaëlle Challet-Bouju; Clémence Cabelguen (BMC, 2024)
Abstract Background Opioid use disorder (OUD) poses a global health challenge, and despite medications for opioid use disorder (MOUD) and psychosocial interventions, relapse remains a significant concern. Comorbid psychiatric disorders, including attention deficit hyperactivity disorder (ADHD), are one of the major factors associated with poor OUD treatment outcome. We aimed to estimate the frequency of probable ADHD (in childhood and in adulthood) in patients with OUD; to assess the factors associated with this comorbidity; and to explore the factors that mediate the relationship between ADHD and OUD treatment outcome. Methods We conducted an observational study using a sample of 229 patients aged 18 years and older who were diagnosed with OUD and had received MOUD for at least six months. Participants were assessed through a structured interview and self-report questionnaires. Multivariate logistic regressions and a mediation analysis were performed. Results Almost half of the participants reported probable ADHD in childhood, and ADHD persisted into adulthood among two-thirds of the patients. The factors associated with poor OUD treatment outcome included earlier onset of OUD, lower education, and greater impulsivity. There was no direct effect of probable ADHD in childhood on OUD treatment outcome, but there was an indirect effect through negative urgency, the tendency to respond impulsively to negatively connoted emotional experiences. Conclusions The findings suggest that ADHD symptoms, particularly impulsivity, may contribute to vulnerability in opioid use and play a crucial role in treatment outcomes for this population. Trial registration: ClinicalTrials identifier NCT01847729.